“Lifestyle” Muslimah - Rinawati, Rini (Mediator, 2007)
It is always interesting to discuss youth lifestyle. As part of pop culture, youth lifestyle has some features, i.e. standardized culture, having fixed repetitive format, light enjoyable, sentimental, short-lasting, and artificially crafted. Such characteristics are in opposite with other cultural values such as serious, intellectuality, time-respect, and authenticity. In the world of Moslem girl, there is also a strong tendency of being modern and sociable. Mass media and globalization are believed to be the most influential factors. In order to solve the problem, original Islamic learning process such as “madrasah” and “pesantren” are strongly promoted.